2016
DOI: 10.1245/s10434-016-5732-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Prognostic Factors for Metachronous Peritoneal Metastasis in Patients with Colon Cancer

Abstract: A proportion of colon cancer patients with metachronous peritoneal metastasis may benefit from combined peritoneal nodule resection and systemic chemotherapy. Right colon cancer, early peritoneal metastasis, a high PCI, and concurrent metastases negatively affected prognosis in patients with metachronous peritoneal metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 45 publications
2
62
1
Order By: Relevance
“…This study is especially specific in that no patients underwent curative surgery, thus eliminating the heterogeneity of perioperative factors. 10 Our study found BL to be an independent predictor of DFS (3and 5-year) and OS (5-year). BL has been reported widely to be significantly associated with poorer post-operative outcomes after CRS-HIPEC.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This study is especially specific in that no patients underwent curative surgery, thus eliminating the heterogeneity of perioperative factors. 10 Our study found BL to be an independent predictor of DFS (3and 5-year) and OS (5-year). BL has been reported widely to be significantly associated with poorer post-operative outcomes after CRS-HIPEC.…”
Section: Discussionsupporting
confidence: 48%
“…PCI has been one of the most consistent independent predictors of morbidity and mortality from CRS-HIPEC. 2,[5][6][7][8][9] There has, however, been no consensus on a PCI cut off in CPM that predicts poorer post-operative outcomes, with studies thus far reporting a wide range (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) that are significantly predictive of DFS and OS. 6,8,[10][11][12] Results from our study suggest that for patients with PC from colorectal primaries, a lower cut-off value of 7-11 is a satisfactorily significant predictor of postoperative OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that 14.1 % of pathologic T4 colon cancer developed metachronous peritoneal metastasis (11) ; therefore, in the present case, metachronous peritoneal metastasis is not unnatural in itself. As it is, solitary distant peritoneal metastasis of colon cancer cephalad beyond the greater omentum similar to the present case has not been reported previously.…”
Section: The Journal Of Medical Investigation Vol 64 August 2017supporting
confidence: 46%
“…Median follow-up time of these patients was 63.6 months. We focused on patients with pT4 disease, a well-known risk factor of peritoneal recurrence, 2,3,6 to ensure that a sufficient number of events were evaluated to determine the clinical impacts of cancer stem cell markers on patient prognosis.…”
Section: Patients and Tissue Specimensmentioning
confidence: 99%